Involvement of connexin43 hemichannel in ATP release after γ-irradiation - Ohshima, Yasuhiro (Oxford University Press, 2012)
Ionizing radiation induces biological effects not only in irradiated cells but also in non-irradiated cells, which is called the bystander effect. Recently, in vivo and in vitro experiments have suggested that both gap junction hemichannel connexin43 (Cx43) and extracellular adenosine triphosphate (ATP) released from cells play a role in the bystander effect. We have reported that γ-irradiation induces ATP release from B16 melanoma cells, which is dependent on the P2X(7) receptor. However, the mechanism of ATP release caused by irradiation remains unclear. We here show the involvement of Cx43 in P2X(7) receptor-dependent ATP release after 0.5 Gy γ-irradiation. Inhibitors of gap junction hemichannels and an inhibitory peptide for Cx43 (gap26), but not an inhibitory peptide for pannexin1 (Panx1), significantly blocked γ-irradiation-induced ATP release from B16 melanoma cells. We confirmed high expression of Cx43 mRNA in B16 melanoma cells. These results suggest involvement of Cx43 in radiation-induced ATP release. We found that after 0.5 Gy γ-irradiation tyrosine phosphorylation was significantly blocked by P2X(7) receptor antagonist, but not gap26, suggesting that tyrosine phosphorylation is a downstream event from the P2X(7) receptor. Since tyrosine kinase inhibitor significantly suppressed radiation-induced ATP release, tyrosine phosphorylation appears to play an important role in the Cx43-mediated ATP release downstream of the P2X(7) receptor. In conclusion, the Cx43 hemichannel, which lies downstream of the P2X(7) receptor, is involved in ATP release in response to radiation. Our results suggest a novel mechanism for radiation-induced biological effects mediated by both ATP and Cx43.